The Interaction of Cold Environment and Carbon Tetrachloride Hepatotoxicity in Mice - Adam, S. E. I. (1970)
A single oral dose of carbon tetrachloride (CCl(4)) of 1 ml./kg. was given to mice maintained at 10° and 20-22°. Cold exposure alone produced fatty changes and depletion of glycogen in the centrilobular zone and modified the liver damage induced by CCl(4) between 5-24 hr after dosing, by increasing lipid accumulation, markedly depleting glycogen, by narrowing the lumina of the sinusoids in the necrotic areas and by producing a large number of ballooned cells in the mid lobular zone. Liver regeneration was rapid in mice kept at room temperature and was complete by 8 days. Depletion of glycogen and fatty infiltration in the centrilobular zone persisted in the liver of mice exposed to cold. The enzymes studied by histochemical techniques were non-specific alkaline phosphatase, adenosine triphosphatase, succinic tetrazolium reductase and glutamate dehydrogenase. Exposure to cold stimulated the sinusoidal alkaline phosphatase activity and depressed the activity of succinic and glutamate dehydrogenases. The early stages of carbon tetrachloride intoxication were accompanied by loss of activities of the latter 2 enzymes. This was more marked on exposure to cold whilst the depressed activity of canalicular adenosine triphosphatase in mice kept at room temperature was absent in those exposed to cold. Necrosis was followed by increased sinusoidal alkaline phosphatase activity and scattered cell reaction in mice kept at both temperatures. There was intense cellular and sinusoidal adenosine triphosphatase activity in mice kept at room temperature and a wider and less intense reaction in these sites in mice exposed to cold. Activities of succinic and glutamate dehydrogenases were diminished in necrotic areas which showed non-specific deposits due to adsorption of enzymes to lipid in mice in both environments. Liver regeneration stimulated the activities of all enzymes although those of succinic and glutamate dehydrogenases remained relatively low in mice exposed to cold environment.